2015
DOI: 10.1007/s00210-015-1175-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimuscarinic-induced convulsions in fasted animals after food intake: evaluation of the effects of levetiracetam, topiramate and different doses of atropine

Abstract: This study evaluated the effects of different doses of atropine and new antiepileptics, levetiracetam and topiramate, on the development of convulsions triggered by food intake in antimuscarinic-treated fasted animals. Mice deprived of food for 24 h and treated i.p. with atropine at a dose of 2.4 or 24 mg/kg developed convulsions after being allowed to eat ad libitum. No convulsions were observed in fasted animals treated with 0.24 mg/kg atropine. There was no difference in the incidence of convulsions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The current study had some limitations: it did not focus on the evaluation of the neuroprotective molecular mechanisms via the antioxidant signaling and receptor binding inhibition mechanisms, did not emphasize the gender-related differences associated with the abnormal phenotypes and effect of the herb on the phenotypes of the mutant flies, and only focused on the effect of the herb on a genetic form of epilepsy while leaving out acquired/induced convulsions like the antimuscarinic and pentylenetetrazole kindling models that are often studied 137 , 162 ; a prospective study will be conducted to assess the practical attributes of antioxidant and receptor inhibition pathways related to the neuroprotective effects of I. cylindrica root extract using bss Drosophila , other genetic models and kindling models of convulsions.…”
Section: Discussionmentioning
confidence: 99%
“…The current study had some limitations: it did not focus on the evaluation of the neuroprotective molecular mechanisms via the antioxidant signaling and receptor binding inhibition mechanisms, did not emphasize the gender-related differences associated with the abnormal phenotypes and effect of the herb on the phenotypes of the mutant flies, and only focused on the effect of the herb on a genetic form of epilepsy while leaving out acquired/induced convulsions like the antimuscarinic and pentylenetetrazole kindling models that are often studied 137 , 162 ; a prospective study will be conducted to assess the practical attributes of antioxidant and receptor inhibition pathways related to the neuroprotective effects of I. cylindrica root extract using bss Drosophila , other genetic models and kindling models of convulsions.…”
Section: Discussionmentioning
confidence: 99%
“…Food deprivation for two days alters the [ 3 H]glutamate binding kinetics in the brain, which was antagonized by antimuscarinic treatment and food intake (Enginar et al, 2003). The other studies with antimuscarinic-induced convulsions showed that, many conventional and new antiepileptic drugs are ineffective in suppressing these convulsions (Enginar et al, 2005;Buget et al, 2016), whereas haloperidol, chlorpromazine, clonidine, tizanidine, and MK-801 were found to be effective (Enginar et al, 1997;.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorpromazine, haloperidol, noncompetitive N-methyl-D-aspartate (MK-801), clonidine and tizanidine provide effective treatments. However, most of the major and new antiepileptic drugs in clinical use are ineffective in suppressing the seizures (1,4). Interestingly, the trigger factors and manifestations of the seizures evoked by eating in patients and fasted animals bear some similarities (5).…”
Section: Introductionmentioning
confidence: 99%